Teachers’ perceptions and beliefs on the use of the Interactive Whiteboard (IWB) in Primary Education - Christoforou, Soteroula (2013)
The Interactive Whiteboard (IWB) is a recent innovation in the Cyprus educational field. Despite their massive adoption in schools, many teachers eventually refuse to integrate their use in their teaching; something that might lead to a failed innovation. Since the IWB’s first implementation in Cyprus schools, there has been little evidence on the teachers’ perceptions about the use of IWBs in class.